Meningkatkan Kepatuhan Minum Obat pada Pasien Tuberculosis Paru Menggunakan Pendidikan Kesehatan berbasis Health Coaching: Improving Medication Compliance in Pulmonary Tuberculosis Patients Using Health Education based on Health Coaching - Mantouw, Frely; Puspitasari, Yenny (Jurnal Abdi Keperawatan dan Kedokteran, 2024)
Problems in patients with pulmonary tuberculosis are often related to non-adherence to treatment and patient boredom with the long treatment process. Sometimes, patients decide to stop treatment because they feel bored and do not recover. This community service program aims to increase medication adherence in pulmonary tuberculosis patients by providing health coaching-based health education. The method uses pre-experiment, pre and post test design designs. This activity was held from April 19, 2024 to May 3, 2024 in the work area of the Seget Health Center, Seget District, Sorong Regency. This program consists of three stages: preparation, implementation, and evaluation. A total of 15 participants participated in this activity. To measure medication adherence, the Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire was used.  The results showed that after being given health coaching-based health education, medication adherence in pulmonary tuberculosis patients increased (53.34%). In conclusion, health coaching-based health education is effective in increasing medication adherence in pulmonary tuberculosis patients.